pengaruh partisipasi anggaran terhadap komitmen organisasi: vale orientation toward innovation sebangai moderasi (studi pada perguruan tinggi swasta di lingkungan kopertis wilayah VI Jawa Tenggah ) - Hernawati Indah Retno (Semantik, 2011)
ABSTRACT: the objective of this study is to examine the role of manager's value orientation towards innovation as moderating variable in the relationship between budgetary participation and organizational commitment. The respondents were middle level managers and lower level managers at the parivate universities in Kopertis VI central of java. out of 400 questionnaires distributed. 71 can be used for analysis, with a response rate of 18 percents. the sampling method used was purposive sampling. Using regression analysis the result of this study indicates that manager's value orientation towards innovation dose not significantly affect as moderating variabel in the relationship between budgetary participation and organizational commitmentKeyword: manager's valueorintation towards innovation: budgetary participation, organizational commitmen, regresssion analysis